'The psychosocial burden of alopecia areata and androgenetica': a cross‐sectional multicentre study among dermatological out‐patients in 13 European countries. (12th November 2019) - Titeca, G.; Goudetsidis, L.; Francq, B.; Sampogna, F.; Gieler, U.; Tomas‐Aragones, L.; Lien, L.; Jemec, G.B.E.; Misery, L.; Szabo, C.; Linder, D.; Evers, A.W.M.; et al.
Abstract: Background: Hair diseases play an important burden on patients' lives, causing significant emotional and psychosocial distress. However, the impairment due to different hair conditions, such as alopecia areata (AA) and androgenetic alopecia (AGA), has rarely been compared. Objective: The aim of this study was to assess the psychological burden of subgroups of patients with different hair diseases and to compare them to a healthy population. Methods: In this study, we analysed a subgroup of patients with hair diseases from patients of a large multicentre study including 3635 dermatological patients and 1359 controls from 13 European countries. In the subgroup of patients with hair diseases, we analysed the socio‐demographic characteristics, the stress level, and the impact of hair diseases on quality of life (QoL), anxiety, and depression and we compared them among patients with AA, AGA and healthy controls. Results: The study population included 115 patients (77% women, 23% men) with hair diseases, 37 of whom with AA and 20 with AGA. Patients with hair diseases had a lower education level than healthy controls (medium educational level: 43% vs. 28%). Overall, 41% of the patients reported stressful life events during the last 6 months compared with 31% of the controls. Patients with the same age, sex, depression level and comorbidities had a worse QoL when suffering from AA than from AGA (Mean Dermatology Life Quality Index score: 5.8 vs. 2.5). Conclusion: Patients with hair diseases are more anxious, depressed and have a lower QoL than controls.